Modernism and the culture of market society - Cooper, John Xiros, 1944- (Cambridge University Press, 2004)
Cooper argues that in their personal relationships, gender roles and sexual contacts, the Modernist avant-garde epitomised the impact of capitalism on everyday life. He explores this provocative theme across a wide range of Modernist authors, including Joyce, Eliot, Stein and Barnes.